2007
DOI: 10.1007/s10535-007-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTLs affecting copper tolerance and the Cu, Fe, Mn and Zn contents in the shoots of wheat seedlings

Abstract: Quantitative trait loci (QTLs) for Cu-tolerance were determined in wheat grown in control and Cu-treated soil in greenhouse. In addition, loci having an influence on the shoot Cu-, Fe-, Mn-and Zn-contents under non-stressed and Cu-stressed environments were mapped. One major QTL for Cu-tolerance was found on chromosome 5DL, while slighter effects were determined on the chromosomes 1AL, 2DS, 4AL, 5BL and 7DS. QTLs affecting the shoot Mn-and Zn-contents were found on the chromosomes 3BL and 3AL, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Modern techniques of molecular biology (Bassam et al 1991, Saghi Maroof et al 1994, Creste et al 2001) and the mapping of rice genome (Chen et al 1997, Temnykh et al 2000, McCouch et al 2002 allow plant scientists to locate the DNA determining the physiological trait that dictate salt tolerance in rice. QTL analysis of physiological traits related to abiotic stresses has been conducted by several researchers (Zhang et al 1995, Koyama et al 2001, Lin et al 2004, Ming et al 2005, Lee et al 2007, Balint et al 2007). Lin et al (2004) reported two major QTLs with very large effects on shoot Na + content (qNA-7) and shoot K + content (qK-1).…”
Section: Introductionmentioning
confidence: 99%
“…Modern techniques of molecular biology (Bassam et al 1991, Saghi Maroof et al 1994, Creste et al 2001) and the mapping of rice genome (Chen et al 1997, Temnykh et al 2000, McCouch et al 2002 allow plant scientists to locate the DNA determining the physiological trait that dictate salt tolerance in rice. QTL analysis of physiological traits related to abiotic stresses has been conducted by several researchers (Zhang et al 1995, Koyama et al 2001, Lin et al 2004, Ming et al 2005, Lee et al 2007, Balint et al 2007). Lin et al (2004) reported two major QTLs with very large effects on shoot Na + content (qNA-7) and shoot K + content (qK-1).…”
Section: Introductionmentioning
confidence: 99%
“…In germinating rice seeds copper stress caused a differential expression of 25 proteins and majority of these proteins were antioxidants or stressrelated proteins (Ahsan et al 2007). Quantitative trait loci (QTLs) affecting the copper tolerance in wheat have also been mapped recently (Bálint et al 2007). …”
mentioning
confidence: 99%
“…speltoides, respectively (McIntosh et al 1982, Gold et al 1999. QTLs for shoot Mn and Cu contents (Bálint et al 2007), for resistance to Fusarium head blight in wheat (Waldron et al 1999) and for resistance to leaf rust (Lr24) in Agropyron elongatum have also been identified on the homoeologous group 3 (Friebe et al 1996a,b). Important QTLs for physiological traits involved in drought tolerance (such as osmotic adjustment and water use efficiency) were also identified on homoeologous group 7 in wheat and barley (Cattivelli et al 2002).…”
Section: Discussionmentioning
confidence: 99%